Rancang Bangun Sistem Informasi Baitulmal “Masjid Jalan Cahaya” Berbasis Website Menggunakan Metode Service Oriented Architecture (SOA): Website-Based Design Of Baitulmal Information System “Masjid Jalan Cahaya” Using Service Oriented Architecture (SOA) Method - Sekarsari Bintang Solehah; Noor Alamsyah; Sri Endang Anjarwani (Journal of Computer Science and Informatics Engineering (J-Cosine), 2024)
Aside from being a center of worship, the mosque can also function as a place to carry out social muamalah worship. Based on the function, of course the mosque has an agenda or charity activities that are held at certain times. It is the same with the fundraising or crowdfunding system run by Baitulmal "Masjid Jalan Cahaya". In its application, the information distributed on social media has not been modified on one platform, there is overlap between program uploads with one another, this is of course an obstacle for donors to find out which mosque programs are running. To answer these needs, this research builds a website-based Baitulmal information system "Masjid Jalan Cahaya" using the Laravel framework which is expected to be a means for mosques to convey all information about costs or funds needed more broadly, quickly, safely, real-time and transparent. In its development, the Baitulmal information system "Masjid Jalan Cahaya" will be integrated with other mosque websites, such as mosque company profiles, Rumah Qur'an and Baitul muamalah mosques, so that continuous system development is needed that makes it easier for each field to carry out data transactions. Departing from this, this information system applies the Service Oriented Architecture (SOA) approach, where this approach develops software using services. In this study, 3 main services were obtained, namely Charity services, Reports, and Tags/Categories. As well as service users for admin, payment and management files which are additional to the baitulmal website. For scalability testing, the System Usability Testing method was used which obtained a result of 87% in the Best Imaginable category, indicating that this system has good quality to use..